HR analytics in an era of rapid automation - Yadav, Radha 1988-; Sinha, Mudita 1982-; Kureethara, Joseph Varghese (Advances in Human Resources Management and Organizational Development (AHRMOD), 2023)
Human Resources (HR) departments often have significant data sets related to employees and positions within their organizations, but optimizing use of this data can present challenges. As the business world rapidly transforms due to technological advancements, experts within the HR domain must learn to effectively use data to improve workforce performance and assist with strategic decisions. A comprehensive understanding of HR analytics and its multiple levels, ranging from descriptive to perspective, can emphasize how the data can support, track, and monitor employee performance, culture, turnover rate, and absenteeism. HR Analytics in an Era of Rapid Automation is a valuable guide for academics, researchers, and practitioners interested in the latest developments in HR analytics. It covers relevant theories and conceptual models based on quantitative and qualitative findings and emphasizes the importance of utilizing HR analytics for sustainable decision making. With a focus on recruitment analytics, talent acquisition, employee performance analytics, and more, this book provides practical solutions to the challenges facing HR professionals in the rapidly changing business world. By highlighting the value of people and HR analytics for business success, this book offers several solutions for the analysis of challenges facing HR professionals today.